Goats with Aprons? A traditional anti-mating innovation used by Maasai communities in Tanzania - Olesikilal, Birikaa; Spinelli, Madison (International Livestock Research Institute, 2024)
A blog post on the use of traditional breeding practices in Tanzania, highlighting the anti-mating apron for goats and sheep.